Mitroanoff Appendicovesicostomy Procedure On Bladder Neck Stenosis: A Case Report - Eko Arianto; Putri Hardianti Kusanto; Ari Astram; Christof Toreh; Frendy Wihono; Stivano R. Torry (International Journal of Health and Pharmaceutical (IJHP), 2025)
The Mitrofanoff Appendicovesicostomy (MAC) procedure is a significant surgical intervention for patients with bladder neck stenosis, particularly in cases of severe urological dysfunction. This case report presents a 34-year-old female with a history of urinary incontinence and vesicovaginal fistula (VVF) following a cesarean section. The patient underwent the MAC procedure to address her bladder neck stenosis and restore urinary continence. Preoperative assessments, surgical techniques, and postoperative outcomes are discussed, highlighting the effectiveness of the MAC procedure in providing a new pathway for urine flow and improving the patient's quality of life. This report emphasizes the importance of a multidisciplinary approach in managing urinary incontinence, considering both physical and psychological factors. It also underscores the need for timely diagnosis and tailored surgical interventions to enhance patient outcomes. Future research should focus on identifying risk factors and developing personalized treatment strategies to mitigate urinary incontinence and related complications in postpartum patients. By integrating clinical evidence and holistic care, healthcare providers can better navigate the complexities of urinary incontinence and improve the quality of life for affected individuals.